Antimicrobial resistance pattern of Streptococci and Staphylococci isolated from cases of bovine clinical mastitis in Nigeria (2012)
Streptococci and staphylococci are frequently isolated from bovine mastitis in dairy cows. Limited information is available on the antimicrobial susceptibility of these organisms in Nigeria. A total of 130 Streptococci and 177 Staphylococci isolated from cases of bovine mastitis from three states in Nigeria namely; Oyo, Kwara and Kaduna states for a period of one year were used in this study. Overall, 55.38% of the strains tested were Streptococcus uberis, 24.62% were Streptococcus agalactiae, 12.31% were Streptococcus dysgalactiae, 3.85% were Streptococcus zooepidemicus, 2.31% were Streptococcus bovis and 1.54% were for Streptococcus equines, 25 coagulase negative staphylococcus and 152 Staphylococci aureus. The antimicrobial susceptibility for these organisms was determined for the following antimicrobial agents: Ampicillin, Tetracycline, Sulphadimidine, Nalidixic acid, Neomycin and Streptomycin. Results demonstrated substantial differences in their resistance patterns for the various organisms. The resistance patterns revealed 10 distinct resistance groups. All the streptococci isolate showed resistance to Ampicillin and tetracycline while 98.46%, 86.15%, 48.46%, 24.62%, and of the Streptoccoci species were resistance to sulphadimidine, Neomycin, Streptomycin and Nalidixic acid respectively while Staphyloccocus aureus had 100% for tetracyclin and sulphadimidine respectively while 97.37%, 88.16%, 69.08% and 67.11% showed resistance to ampicillin, neomycin, nalidixic acid and streptomycin respectively. However, Staphylococcus coagulase negative showed 100% resistance to tetracycline and sulphadimidine while 72%, 68%, 68%, and 32% showed resistance to nalidixic acid, neomycin, ampicillin and streptomycin respectively. The result of this study revealed that dairy farmers misused these antibiotics by treating cows several times per case. This study point to the fact that dairy farmers should take caution in the use of antibiotics for the dairy cows on the farms